Dual-Role Marketing Strategy in Military Hospitals: Bridging Institutional Military Objectives and Civilian Healthcare Needs - Hanii Ammariia; Muhardi Muhardi; Sri Suwarsi (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
This study examines the effectiveness of dual-role marketing strategies in Indonesian Army hospitals in West Java, which are required to simultaneously fulfill national defense mandates and provide public healthcare services. Despite growing attention to public-sector marketing, integrative analyses that address the intersection of military and civilian service roles remain limited. The research adopts a qualitative literature review approach, drawing on international journal articles, scholarly books, and policy documents related to healthcare marketing and military institutions. Through this approach, the study synthesizes existing knowledge to identify key factors influencing the success of dual-role marketing. The findings reveal that the effectiveness of dual-role marketing is shaped by three primary factors. First, strengthening military institutional identity serves as a source of differentiation and enhances service credibility. Second, the application of public service–oriented marketing principles improves public trust, accessibility, and community engagement. Third, adaptive organizational governance is essential to align military operational demands with the expectations of civilian healthcare users. In conclusion, the success of marketing strategies in Indonesian Army hospitals depends on their ability to maintain a dynamic balance between defense functions and public service responsibilities. This study contributes to the conceptual advancement of public-sector marketing by integrating military and healthcare perspectives, while also offering practical insights for policymakers and hospital administrators in optimizing service delivery within dual-role institutional contexts.